A Literature Review of Word of Mouth and Electronic Word of Mouth: Implications for Consumer Behavior - Huete-Alcocer, Nuria (Frontiers in Psychology, 2017)
The rise and spread of the Internet has led to the emergence of a new form of word of mouth (WOM): electronic word of mouth (eWOM), considered one of the most influential informal media among consumers, businesses, and the population at large. Drawing on these ideas, this paper reviews the relevant literature, analyzing the impact of traditional WOM and eWOM in the field of consumer behavior and highlighting the main differences between the two types of recommendations, with a view to contributing to a better understanding of the potential of both.